Color Grading sebagai Pembangun Mood pada Setting Waktu dalam Web Series Rewrite - Shabira Almaas Yanaayuri; I Putu Suhada Agung (Texture:Art and Culture Journal, 2022)
Color  grading  can  be  used  to  support  the  film’s  narrative  by  creating  an  atmosphere  or  mood  that complements the storyline. This study aims to analyze and describe color grading as a mood builder that is applied to time settings in Web Series Rewrite. The results of this study found that color grading in several scenes at each time setting in Web Series Rewrite is used to build the mood or atmosphere in the story. The colors that are widely used include blue and brown with a mixture of other colors, namely: red, gray and black. Light blue is used to build the atmosphere of a scene that seems cold and melancholy, brown is used to build the atmosphere of a scene that seems warm, and dark brown and reddish brown tend to build a dark atmosphere and angry conflict. The use of gray color gives a gloomy and sad impression.